An experimental investigation on nano-TiO2 and fly ash based high performance concrete - Martins, Tiago Manuel da Rocha (2016)
High performance concrete (HPC) offers several advantages over normal-strength concrete, namely, high mechanical strength and high durability. Therefore, HPC allows for concrete structures with less steel reinforcement and a longer service life, both of which are crucial issues in the eco-efficiency of construction materials. Nevertheless international publications on the field of concrete containing nanoparticles are scarce when compared to Portland cement concrete (around 1%) of the total international publications. HPC nanoparticle-based publications are even scarcer. This article presents the results of an experimental investigation on the mechanical properties and durability of HPC based on nano-TiO2 and fly ash. The durability performance was assessed by means of water absorption by immersion, water absorption by capillarity, ultrasonic pulse velocity, electric resistivity, chloride diffusion and resistance to sulphuric acid attack. The results show that the concretes containing an increased content of nano-TiO2 show decreased durability performance. The results also show that concrete with 1% nano-TiO2 and 30% fly ash as Portland cement replacement show a high mechanical strength (C55/C67) and a high durability. However, it should be noted that the cost of nano-TiO2 is responsible for a severe increase in the cost of concrete mixtures.